PRESERVATION OF DIGITIZED INTANGIBLE CULTURAL HERITAGE IN MUSEUM STORAGE - Erturk, Nevra (GELENEKSEL YAYINCILIK LTD STL, 2020)
Conservation, research and communication are the basic functions of the museums according to the new museological approach, and conservation is one of the core missions since the birth of the museums. On the other hand, collections are the hearth of the museums and contribute to their development and activities. Storage areas protect collections and provides sustainability for the collection management. In this context, one of the main duties of museums is to maintain and manage collections in storage area under appropriate and safe conditions. Most of the museums in the world exhibit only a small percentage of their collections and so many collection items are housed in storage. Storage areas require regular monitoring, control and maintenance similar to exhibition galleries. Physical and environmental conditions of storage areas, storage systems and methods differ according to the material, condition, quantity and dimensions of the museum collections. Museum collections are defined as movable, immovable as well as tangible and intangible cultural heritage. Today, digital heritage is also part of the collections. Digital museum collections can be defined as born digital, digital or digitized item. Collecting, conservation, documentation, accessing or storage procedures of movable or tangible heritage in museums are on practice with well-developed principles, standards as well as collection management and conservation policies. However, identification, documentation, the concept of authenticity or issues of ownership of intangible cultural heritage is still on discussion. Digital preservation is also one of the recent research topics and practices for safeguarding of the intangible cultural heritage. In this context, digitized intangible cultural heritage can defined as digital resources that are digitized from audio-visual recordings, photographs or ephemera which documents and preserves practices and their tools or spaces associated with. However, technology is developing much faster today and most of the digital tools have a very short life span. Thus, technological development is a challenge for preserving digitized intangible cultural heritage. In a broader sense, preservation of digital heritage in the museum storage areas including physical and environmental conditions of the storage area where the digital heritage is located, their storage system, method and the storage management procedures are different comparing to the preservation of tangible heritage or other movable cultural assets. In this framework, main research questions of this article are: How the digitalization practices contribute to the safeguarding of the intangible cultural heritage? As technology is changing rapidly, how the preservation tools and storage methods of the digitized intangible cultural heritage can be kept up with the technological developments? How long the life span of the digitized intangible cultural heritage collections can be extended in museum storage? The article will mainly focus on the storage management of digitized intangible cultural heritage, and explain their physical and environmental conditions in the museum storage area. Terms of digital heritage, digitized intangible cultural heritage, digital preservation as well as the history of digital preservation of museum collections, organizations/institutions' contributions in the field will be discussed. Information about the storage system, storage method with safe materials and procedures will be provided within the scope of literature review. The paper highlights contributions of the digitalization practices to the safeguarding of the intangible cultural heritage, major issues and challenges related to the digital preservation in museum storage, and propose steps for the sustainable storage management of digitized intangible cultural heritage.
Keywords: Digital preservation; digital heritage; digitized intangible cultural heritage; museum storage management; preventive conservation; Arts & Humanities - Other Topics